2022
DOI: 10.3390/biomedicines10030672
|View full text |Cite
|
Sign up to set email alerts
|

Effect and Mechanisms of Antibacterial Peptide Fraction from Mucus of C. aspersum against Escherichia coli NBIMCC 8785

Abstract: Peptides isolated from the mucus of Cornu aspersum could be prototypes for antibiotics against pathogenic bacteria. Information regarding the mechanisms, effective concentration, and methods of application is an important tool for therapeutic, financial, and ecological regulation and a holistic approach to medical treatment. A peptide fraction with MW < 10 kDa was analyzed by MALDI-TOF-TOF using Autoflex™ III. The strain Escherichia coli NBIMCC 8785 (18 h and 48 h culture) was used. The changes in bacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 62 publications
1
16
0
Order By: Relevance
“…In the region above 100 kDa, proteins might correspond to glycoproteins and mucins. More details on the C. aspersum mucus composition based on our earlier studies [ 15 , 18 , 19 , 25 , 26 , 27 ] are presented in Table 1 . A number of new peptides have been isolated from the mucus, and their amino acid sequences were determined by de novo sequencing and by MALDI-TOF-MS/MS analyses; some of them are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the region above 100 kDa, proteins might correspond to glycoproteins and mucins. More details on the C. aspersum mucus composition based on our earlier studies [ 15 , 18 , 19 , 25 , 26 , 27 ] are presented in Table 1 . A number of new peptides have been isolated from the mucus, and their amino acid sequences were determined by de novo sequencing and by MALDI-TOF-MS/MS analyses; some of them are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Trapella et al [ 16 ] also suggested that snail mucus’s potential as a therapeutic agent in wound repair was attributable to the synergistic activity of several molecules. In mucus, such as we have used in the present paper, the primary structures of novel antimicrobial peptides with molecular weights mainly between 1–3 kDa were identified by tandem mass spectrometry ( Table 1 ), and their antibacterial activity was demonstrated [ 18 , 26 ]. The C. aspersum mucus contains both cationic and anionic and neutral peptides, but cationic are dominant.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations